Human relations in organizations : applications and skill building - Lussier, Robert N. (McGraw-Hill/Irwin, 2013)
Suitable for instructors who want to incorporate activities and exercises into the classroom, and benefits students who want to understand concepts as well as apply and develop skills that they can use in their daily and professional lives, this title provides an understanding of human relations/organizational behavior concepts